2018
DOI: 10.1016/j.jtrangeo.2018.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Changing travel behaviour and attitudes following a residential relocation

Abstract: A considerable amount of studies have indicated that people to some extent select themselves in specific neighbourhoods allowing them to travel in their desired way. Although a lot of studies analysed the degree to which travel preferences affect the residential location choice, few studies looked at the effect of a residential relocation on people's travel behaviour and attitudes. A new residential context has the potential to disrupt previous travel choices and could potentially change people's attitudes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(54 citation statements)
references
References 50 publications
3
51
0
Order By: Relevance
“…For instance, George who has reached a sensitive age for bicycling prioritized the value of security over environmentalism and thus changed his commuting from many years of bicycling to car use after the relocation of his workplace. This finding is in line with the results from De Vos, Ettema [64], who suggest that travel attitudes are likely to change after relocation. Using a quantitative analysis, this study suggests that travel attitudes vary across individuals depending on the spatial characteristics of the current and previous locations.…”
Section: Convenience and Speed Weigh Way Moresupporting
confidence: 91%
See 1 more Smart Citation
“…For instance, George who has reached a sensitive age for bicycling prioritized the value of security over environmentalism and thus changed his commuting from many years of bicycling to car use after the relocation of his workplace. This finding is in line with the results from De Vos, Ettema [64], who suggest that travel attitudes are likely to change after relocation. Using a quantitative analysis, this study suggests that travel attitudes vary across individuals depending on the spatial characteristics of the current and previous locations.…”
Section: Convenience and Speed Weigh Way Moresupporting
confidence: 91%
“…Dissonance between behavior and attitude/value not only concerns travel mode choices, which is increasingly studied [14,15,43], but also pertains to longer-term travel-related decisions such as residential location choice [64]. For instance, a mismatch between one's actual neighborhood type and their preferences regarding physical attributes of a residential neighborhood can result in residential dissonance [55].…”
Section: Dissonance In Travel-related Choicesmentioning
confidence: 99%
“…In the end, 1,842 adults participated, of which 1,650 respondents -who completed the survey -were used in this study (resulting in a response rate of 16.5%). For more details on the neighbourhood selection and sampling recruitment, see De Vos et al (2018).…”
Section: Datamentioning
confidence: 99%
“…In most cases, moving to more urban neighbourhoods will therefore reduce household car possession, while moving to a suburban neighbourhood will increase car possession, further stimulating a modal shift (Aditjandra et al, 2016;Scheiner & Holz-Rau, 2013). Two recent studies also indicate that people relocating to a new neighbourhood will improve their attitudes towards travel modes stimulated by the new built environment (De Vos et al, 2018;Wang & Lin, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Long-term life decisions, such as residential relocation can influence changes in travel behaviour and attitudes (De Vos, Ettema, & Witlox, 2018;Van der Waerden, Borgers, & Timmermans, 2003). For instance, Handy et al (2005) observed significant changes in travel mode and car travel distances after housing relocation.…”
Section: Self-selection: a Joint Model Of Residential Location And Trmentioning
confidence: 99%